Jedność w różnorodności: uroczystość Niepokalanego Poczęcia Najświętszej Maryi Panny w liturgii rzymskiej i hiszpańsko-mozarabskiej - Gutowski, Tomasz (Verbum Vitae, 2025)
The article addresses the historical-theological formation of the Feast of the Immaculate Conception of the Blessed Virgin Mary in two liturgical traditions: Roman and Hispano-Mozarabic. The analysis focuses on the origins of the feast, its evolution, and the specific characteristics of the liturgical texts associated with this celebration in both rites. The structure of the study includes an introduction, two main sections, and conclusions. The first part is devoted to the history of the feast and the analysis of contemporary liturgical texts in the Roman rite. The second part addresses analogous issues in the Hispano-Mozarabic rite. The conclusions provide a comparison of the two traditions, highlighting both common theological themes and differences arising from distinct liturgical emphases. The analysis employs an analytical method, focusing solely on the missal texts of both rites, excluding biblical readings and breviary texts. The key materials were studies compiling existing literature on the subject. The main conclusion indicates that the Roman and Hispano-Mozarabic liturgies express the same truth of faith and its central theological themes, albeit with slightly different emphases. The theological unity, alongside liturgical diversity, underscores the richness of the Church and its capacity to integrate traditions that mutually enrich one another.